EFFECT OF COW TESTICULAR FLOUR EXTRACT WITH DIFFERENT DOSES ON THE SUCCESS OF KOI KOHAKU FISH MASCULINIZATION (Cyprinus carpioLinn.) - Faraz Ramadhan; Netti Aryani; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis research has been conducted in March - June 2020 at the Fish Breeding and Breeding Laboratory of the Faculty of Fisheries and Marine, Riau University. This study aims to found out the best influence and dosage of Cow Testicular Flour Extract in the success of masculinization of Koi Kohaku fish larvae. While the expected benefits can provide information on the masculinization of Koi Kohaku fish larvae using Cow Testicular Flour Extract (CTFE) against the success of increasing the sex ratio of male fish. The method used in the study was the Complete RandomIzed Design (CRD) method with five levels of treatment with three repeats. The treatment consists of soaking Cow's Testicular Flour (CTF) with a dose of 0 mg/L of water, a dose of 60 mg/L of water, a dose of 80 mg/L of water, a dose of 100 mg/L of water and a dose of 120 mg/L of water. Based on the results of the research that has been done, it can be concluded that the best dose of CTFE was obtained at P4 (TTS 120 mg/L) of 73.33% and life-size of 90%. The results of water quality measurement during the study were temperature of 27 - 28 oC, water pH of 6.2 - 7.4 and oxygen of 6.5 - 7.4 mg / L.    Keywords: Koi Kohaku Fish, Masculinization, Cow Testicles Flour